2006
DOI: 10.1097/00005721-200603000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The NICU Experience of Lactation and Its Relationship to Family Management Style

Abstract: The family management style of lactation, which can be easily ascertained by interviewing families, may be a useful tool in planning appropriate interventions to promote lactation success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 15 publications
1
38
0
4
Order By: Relevance
“…Babies were aged 3-9 months. The women were either still BF or had weaned recentlyInterpretative phenomenological analysis Semi-structured interviews using an interview guideBernaix et al 2006, USAThe parents' management of the lactation experience 9 sets of parents of premature infants aged 24-32 weeks gestation. Infants were all in the Neonatal Unit and parents planned to BF.…”
mentioning
confidence: 99%
“…Babies were aged 3-9 months. The women were either still BF or had weaned recentlyInterpretative phenomenological analysis Semi-structured interviews using an interview guideBernaix et al 2006, USAThe parents' management of the lactation experience 9 sets of parents of premature infants aged 24-32 weeks gestation. Infants were all in the Neonatal Unit and parents planned to BF.…”
mentioning
confidence: 99%
“…She concluded that her study results provided the basis for developing and testing interventions that advanced practice nurses could use with breast-feeding families of low-birth-weight infants. Bernaix, Schmidt, Jamerson, Seiter, and Smith (2006) studied breast-feeding of premature neonates in a neonatal intensive care unit and confirmed Krouse's typology of FMSs.…”
Section: Research Related To Fmssmentioning
confidence: 63%
“…Past qualitative research on the determinants of breast milk feeding in the NICU found that parents of children in the NICU had to confront "altered expectations" of breastfeeding upon the unexpected premature delivery (Bernaix et al, 2006). If a premature delivery was somewhat expected, either through early designation of a high-risk pregnancy, the presence of multiples, or interaction with a community with high premature birth risk, mothers were more inclined to research breast milk feeding information during pregnancy and indicate they felt "more prepared" (Bernaix et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…If a premature delivery was somewhat expected, either through early designation of a high-risk pregnancy, the presence of multiples, or interaction with a community with high premature birth risk, mothers were more inclined to research breast milk feeding information during pregnancy and indicate they felt "more prepared" (Bernaix et al, 2006). Other qualitative studies point to a mother's concerns with social support (Kaufman and Hall, 1989), adequate supply, and "problems with the mechanics of breastfeeding a preterm infant" as potential barriers to breast milk feeding (Kavanaugh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%